Innowacyjność jako czynnik wzrostu konkurencyjności regionu - Skonieczny, Jan; Świda, Adam (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The article focuses on the competitiveness of European region. The main elements of the competitiveness are innovations. The authors tried to explain the nature of innovations, their measures and their influence on regional development. For better understanding, some limitations of the measuring process have been explained. The article contains many empirical research results.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 602-610